The Influence of Attitudes, Actions, and Sympathy in Primary Service on Employee Performance Productivity Malang City Population and Civil Registration Office - Maria Rosiana Pulo Tukan; Gunawan, Cakti Indra; Moh. Askiyanto (International Journal of Management and Business, 2025)
Human resource development is also part of management to succeed and achieve organizational goals, to provide satisfactory (excellent) service to consumers. In government institutions, the attitudes, actions, and sympathies of employees are part of the excellent service that must be provided to the community. Public sector performance productivity is essential to be carried out to advance the organization effectively and efficiently. This study aims to determine the influence of attitudes, actions, and sympathy on the productivity of the performance of employees of the Malang City Population and Civil Registration Office. This study uses quantitative approaches and multiple linear regression as data analysis methods using the SPSS program. The sample of this study was determined using the Probability Sampling method. The researcher used questionnaires as a data collection technique.  The results of the research and its analysis prove that the attitude of excellent service has a positive effect on the productivity of employee performance of the Population and Civil Registration Office of Malang City, actions in excellent service not only have a positive effect but have a dominant effect on the productivity of employee performance of the Population and Civil Registration Office of Malang City, and also sympathy for excellent service positively affects employee performance productivity of the Population and Civil Registration Office of Malang City